Hydrogel Microellipsoids that Form Robust String‐Like Assemblies at the Air/Water Interface. Issue 22 (25th April 2019) - Honda, Kenshiro; Sazuka, Yuka; Iizuka, Kojiro; Matsui, Shusuke; Uchihashi, Takayuki; Kureha, Takuma; Shibayama, Mitsuhiro; Watanabe, Takumi; Suzuki, Daisuke
Abstract: Soft colloidal particles such as hydrogel microspheres assemble at air/water or oil/water interfaces, where the soft colloids are highly deformed and their surface polymer chains are highly entangled with each other. Herein, we report the formation of robust one‐dimensional, string‐like colloidal assemblies through self‐organization of hydrogel microspheres with shape anisotropy at the air/water interface of sessile droplets. Shape‐anisotropic hydrogel microspheres were synthesized via two‐step polymerization, whereby a hydrogel shell was formed onto preformed rigid microellipsoids. The shape anisotropy of the hydrogel microspheres was confirmed by transmission electron microscopy and high‐speed atomic force microscopy as well as by light‐scattering measurements. The present findings are crucial for the understanding of natural self‐organization phenomena, where "softness" influences microscopic assembled structures such as those of Nostoc bacteria. Abstract : The self‐organization of anisotropic hydrogel microspheres at the air/water interface of sessile droplets results in robust string‐like colloidal assemblies. The softness of the microellipsoids influences the geometrical stability of the assembled structures. The robustness of these soft hydrogel microellipsoid assemblies arises from the interpenetration of the hydrogel layer at the air/water interface.